History, society, and land relations : selected essays - Namboodiripad, E. M. S. (LeftWord Books, 2010)
This puts together Namboodiripad's essays spanning six decades, from 1937 to 1996. Included are classic essays such as 'The Question of Land Tenure in Malabare,' 'A Short History of the Peasant Movement in Kerala,' 'Caste Conflict versus Growing Unity of Popular Democratic Forces', Marxism, Leninism and Bourgeouis Judiciary,' among others.